Estudo numérico e experimental das propriedades elétricas das columbitas ZnNb2O6, CaNb2O6 e seus compósitos para aplicações em componentes de alta frequência - Barros, Helenilson de Oliveira (2024)
In recent years, the demand for wireless technology has boosted research in the areas of telecommunications engineering and materials engineering. Increasingly speedy communication devices, wireless charge transfer, military radars and autonomous weapons are small examples of the infinite application of this promising technology. In this context, the synthesis of materials that can operate in the microwave region of the electromagnetic spectrum is of great interest and attracts attention in the areas of materials chemistry and solid-state physics. Thus, the study carried out here aimed at the synthesis and characterization of zinc niobate (ZnNb2O6), ceramic matrices with different additions of calcium titanate (CaTiO3), ZNO(1-x)-CTOx,(x = 0; 0.1; 0.2; 0, 4 and 0.45 values in mole fraction) using the conventional solid state method for the synthesis of these materials. After obtaining the samples, the dielectric properties in the microwave and radio frequency region and their characteristics for use as a dielectric resonator antenna and as electronic components were analyzed. For this purpose, the cylindrical shape was chosen to study the electrical modes. After the sintering process of the ceramic pieces, the X-ray diffraction (XRD) technique was used for structural characterization, identifying the desired phase in the ZNO matrix and the phases formed from the additions. The scanning electron microscopy (SEM) technique provided information about the morphology that helped to understand the densification and permittivity responses, showing, in some cases, the formation of overlapping layers with the addition of CTO. The thermal stability of the samples was measured experimentally through the study of the resonant frequency temperature coefficient () at different temperatures, the results confirmed an improvement in the thermal stability of the composites with values between -88.95 to -8.16 ppm/ºC. The method developed by Hakki-Coleman was used to obtain dielectric properties in the microwave range, such as dielectric constant (εr) and loss tangent (tg-δ), of all samples. The properties in the radio frequency region were analyzed using the impedance spectroscopy technique using the electrical modulus, conductivity and real and imaginary impedance quantities, in addition to measuring activation energy, permittivity and Nyquist diagram. The addition of CTO caused a slight increase in the dielectric properties of the composites, such as permittivity, in relation to the pure sample, while the addition of CTO to the composite decreased the dielectric loss, in addition to decreasing the activation energy for the thermally stable samples. The numerical simulation demonstrated the material's functioning as a dielectric resonator antenna (DRA), with a return loss below -10 dB, gain ranging from 4.5 to 6 dBi and radiation efficiency above 96% in all samples.